Ryder 2019 - Meteorological, Oceanographic and Ship Data Collected Onboard Icebreaker Oden - Ship-Based Research Support, Swedish Polar Research Secretariat (Swedish Polar Research Secretariat, 2021)
Ryder 2019 was a research expedition on board the Swedish icebreaker Oden to the remote Ryder Glacier in northwest Greenland. The data presented here are the meteorological, oceanographical and ship data collected onboard Oden during the expedition.

The Ryder 2019 expedition with the Swedish icebreaker Oden was a multidisciplinary expedition, spanning the fields of atmospheric chemistry and physics, biology, climatology, ecology, genomics, glaciology, oceanography, marine geology, geophysics, geochemistry and archaeology. The overarching goal was to investigate the dynamics and development of the marine cryosphere and ocean conditions over time in the marine realm of Ryder Glacier; more specifically in the Sherard Osborn Fjord and adjacent area of northern Nares Strait and the southern Lincoln Sea. Earth’s marine cryosphere includes glaciers extending into the ocean, ice sheets with their base suppressed below sea level, sea ice, gas hydrates and subsea permafrost.

Scientific motivation:
One of the primary scientific motivations of the expedition is related to the role of outlet glaciers, such as Ryder Glacier, draining the Greenland Ice Sheet into the ocean. The dynamics of Greenland’s outlet glaciers represent an essential, but poorly constrained, part of our understanding of future sea-level rise in a warming climate. Critical to their stability are the roles of sea ice, floating ice tongues, bedrock and the shape of the seafloor.

The goal was to collect contextual data including information about the physical shape of the seafloor and its uppermost structure and geological composition, ocean conditions, as well as information about meltwater influx from the glaciers in the survey area. These data are needed from this poorly explored region to better constrain the numerical models needed to predict and assess the potential contribution of northern Greenland’s Ice Sheet to future sea-level rise.

This data set contains meteorological, oceanographical and ship data collected onboard IB Oden during the expedition Ryder 2019, which was an international research cruise to the Arctic Ocean.

Meteorological variables: Air temperature, Humidity, Wind direction/speed, Atmospheric pressure, Cloud height/cloudiness, Photosynthetic Active Radiation (PAR).

Oceanographical variables: Sea water temperature, Conductivity, Salinity and Sound velocity.

Ship data: Position, Speed, Course, Heading, Water depth.

A "Parameter list" which describes the dataset is attached.

Quality Information: No quality check or other processing of the data has been undertaken. Users should be aware of this in further data handling and analysis.

Sommaren 2019 genomfördes en forskningsexpedition med isbrytaren Oden till den svårtillgängliga Ryderglaciären i nordvästra Grönland. De data som presenteras här är meteorologiska och oceanografiska data, samt skeppsdata, insamlade ombord på Oden under expeditionen.

Ryder 2019 med den svenska isbrytaren Oden var en tvärvetenskaplig expedition som spänner över forskningsområden som atmosfärskemi och fysik, biologi, klimatologi, ekologi, genforskning, glaciologi, oceanografi, maringeologi, geofysik och geokemi samt arkeologi. Det övergripande målet var att undersöka den marina kryosfärens och havsförhållandenas dynamik och utveckling över tid i området kring Ryderglaciären – mer specifikt i Sherard Osborn Fjord och närliggande områden i norra Nares sund och södra Lincolnhavet. Den marina kryosfären omfattar glaciärer som sträcker sig ut i havet, istäcken med sin bas nedtryckt under havsnivå, havsis, gashydrater och permafrost i havsbotten.

Vetenskaplig målsättning:
En av de främsta målsättningarna med expeditionen är kopplad till den roll som utlöparglaciärer, till exempel Ryderglaciären, spelar för den grönländska inlandsisens dränering ut i havet. Utlöparglaciärernas dynamik är en viktig del för vår förståelse av hur framtida havsnivåhöjning kan utvecklas i ett varmare klimat. Havsis, shelfis, berggrund och havsbottens form spelar en avgörande roll för utlöparglaciärernas stabilitet.

Målet var att samla in kontextuell data, inklusive information om havsbottens djup och fysiska form samt dess översta struktur och geologiska sammansättning, oceanografiska förhållanden samt information om inflödet av smältvatten från glaciärerna i området. Data från det här sällan undersökta området behövs för att kunna förbättra de numeriska modeller som används för att förutse och bedöma vilken potentiell påverkan inlandsisen på norra Grönland kan ha för framtida havsnivåhöjning.

Data innehåller meteorologiska och oceanografiska data, samt skeppsdata, insamlade ombord på isbrytaren Oden under forskningsexpeditionen Ryder 2019.

Meteorologiska variabler: Lufttemperatur, luftfuktighet, vindriktning/-hastighet, lufttryck, molnhöjd/molnighet, fotosyntetiskt aktiv strålning (PAR).

Oceanografiska variabler: Havsvattentemperatur, konduktivitet, salthalt, ljudhastighet.

Skeppsdata: Position, fart, kurs, stävad kurs, vattendjup.

En ”Parameter list” finns bilagd som beskrivning av data.

Data har inte genomgått kvalitetsgranskning. Användare behöver ta hänsyn till det i all hantering och vidare analys.
Ryder 2019 - Meteorologiska och oceanografiska data, samt skeppsdata, insamlade ombord på isbrytaren Oden
Keywords: ATMOSPHERE; ATMOSPHERIC WINDS; WIND SPEED; WIND DIRECTION; VISIBILITY; WEATHER EVENTS; ATMOSPHERIC TEMPERATURE; AIR TEMPERATURE; PRECIPITATION AMOUNT; PRECIPITATION RATE; HUMIDITY; CLOUD FREQUENCY; CLOUD BASE HEIGHT; ATMOSPHERIC PRESSURE; SEA LEVEL PRESSURE; ATMOSPHERIC PRESSURE MEASUREMENTS; SALINITY/DENSITY; SALINITY; CONDUCTIVITY; PHOTOSYNTHETICALLY ACTIVE RADIATION; WATER TEMPERATURE; WATER DEPTH; Atmospheric conditions; Atmosfäriska förhållanden; Coordinate reference systems; Referenskoordinatsystem; Hydrography; Hydrografi; Meteorological geographical features; Geografiska meteorologiska förhållanden; Oceanographic geographical features; Geografiska oceanografiska förhållanden; Natural Sciences; Naturvetenskap; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Geoscientific Information; Geovetenskap; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi; Oceans; Kust och hav; Location; Positionering